Guided Inquiry Based Physics E-Module to Enhance Students’ Conceptual Understanding and Learning Attitudes: A Literature Review - Edo Juniarsyah; Tri Ariani (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
This study aims to review the quality of guided inquiry-based learning module development and its contribution to students’ scientific literacy, academic language use, and discourse-based conceptual understanding in Physics learning. The method employed was a literature review examining 50 articles on guided inquiry-based learning material development published between 2018 and 2025. From these, 10 of the most relevant articles were selected using the PRISMA procedure for in-depth analysis through content analysis techniques. The results indicate that various learning products, including modules, e-modules, worksheets, digital comics, and interactive learning media, achieved very valid and very practical categories based on evaluations by experts, teachers, and students. Furthermore, guided inquiry-based learning consistently supports the development of students’ conceptual understanding as reflected in their ability to interpret scientific texts, construct explanations, use scientific terminology appropriately, and engage in argumentation, as well as fostering positive learning attitudes manifested through increased engagement, collaborative communication, and reflective discourse during learning activities. In conclusion, guided inquiry-based learning modules are feasible for implementation and demonstrate strong potential in enhancing the quality of Physics learning, particularly in promoting students’ scientific literacy and language-mediated learning processes across various educational levels.